Hubungan Antara Gaya Hidup Hedonis dengan Perilaku Konsumtif pada Mahasiswa Psikologi di Universitas Sahid Surakarta - Aldila Andari Kristi; Dhian Riskiana Putri; Anniez Rachmawati Musslifah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study was conducted with the aim of finding out the relationship between hedonistic lifestyle and consumptive behavior in psychology students at Sahid University Surakarta. Sampling was carried out using a simple random sampling technique with a total of 33 students. The purpose of this study is to find out whether there is a relationship between hedonistic lifestyle and consumptive behavior in psychology students at Sahid University Surakarta. The method that will be used to test the hypothesis in this study uses the Pearson correlation test with the Pearson product moment correlation technique. The results of this study showed that there was no relationship between hedonistic lifestyle and consumptive behavior in psychology students at Sahid University Surakarta with a value of r = 0.135, with p = 0.455. Based on these results, the hypothesis in this study is rejected, which means that the lower the hedonistic lifestyle of students, the higher the consumptive behavior of students, and vice versa, the higher the hedonistic lifestyle of students, the lower the consumptive behavior of students.